Lens fibers have a fully functional ubiquitin-proteasome pathway - Pereira, Paulo (2003)
We previously showed that lens epithelial cells have a fully functional ubiquitin-proteasome pathway (UPP) and that ubiquitin-conjugating activity is up-regulated in response to oxidative stress. In this study we assessed the protein levels and activities of different components of the UPP in lens fibers. Calf lenses were dissected into four different regions: epithelial layer, outer cortex, inner cortex and nucleus. Relative levels of ubiquitin-activating enzyme (E1), ubiquitin-conjugating enzymes (E2s), endogenous ubiquitin conjugates, 19S and 20S proteasome subunits were determined by Western blotting. The activities of E1 and E2 were determined by thiol ester assays and the activities of the proteasome and isopeptidases were determined using ubiquitinated [alpha]-lactalbumin as a substrate. This work demonstrates that lens fibers, including those in the nuclear region, contain most, if not all, of the components for the UPP. Ubiquitin conjugation activity, proteasome activity and isopeptidase activity were also detected in all layers of the lens. The reduced ubiquitin conjugation activity in the inner regions of the lens appeared to be due to a decline in levels of a specific family of E2s, Ubc4 or Ubc5, which were shown to be the rate-limiting enzymes for the formation of high mass conjugates in the lens. Supplementation of Ubc4 or Ubc5 can partially restore the ubiquitin conjugation activity in the inner regions of the lens. Since Ubc4 and Ubc5 are involved in selectively ubiquitinating damaged or abnormal proteins, the decline in levels and activities of these E2s may be responsible for the accumulation of abnormal proteins in inner regions of the lens.